Medical Waste Management: A Case Study on Rajshahi City Corporation in Bangladesh - Alam, MZ; Islam, MS; Islam, MR (Journal of Environmental Science and Natural Resources, 2015)
The management of medical waste (MW) is of great importance due to its impact on human health and environment. The present practices of improper management of generated medical wastes in different Healthcare Establishment (HCEs) in Rajshahi City Corporation (RCC) is playing a contributing role to create vulnerable condition in spreading out the Diarrhea, Hepatitis and various skin related diseases. The objectives of the study are to identify different types of wastes, its generation rate and assess the existing waste management in various HCEs. The study was carried out in 14 different HCEs that generated much portion of MW of total generated MW in RCC. The methodology of this project was descriptive and consisted of the use of field survey and interviews with the relevant authorities and personnel involved in the management of MW. It was found that the surveyed HCEs generate a total of 1495 kg/day of MW; of which about 1328.6 kg/day (88.87%) are non-infectious and about 166.4 kg/day (11.13%) are infectious. The average waste generation rate for surveyed HCEs is 1.54 kg/bed/day or 0.30 kg/patient/day. It was found from the survey that there is no proper and systematic management of medical wastes. The study reveals that lack of awareness; financial support and willingness are responsible for improper management of MW. So the RCC and HCEs authorities should adopt appropriate policy regarding this issue and provide training program on relevant personnel who are engaged in medical waste management. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22062 J. Environ. Sci. & Natural Resources, 6(1): 173-178 2013